Mining and Its Impact on Economic Development in Colombia - Fuentes López, Héctor Javier; Ferrucho-Parra, Cindy Carolina; Martínez-González, William Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2021)
This paper presents a theoretical and empirical analysis of the relationship between mining and development in Colombia, taking as reference the years 2016 and 2017. The historical process of mining in Colombia is studied to understand its significance and its spatial correlation with social variables. Based on institutionalist concepts and the use of panel data models, the aim is to determine that the effects that mining activity in Colombia has had on social variables such as the Human Development Index, the GINI coefficient, and poverty are caused by institutional variables such as municipal performance, instead of by variables related to mining such as mining GDP. It is found that mining has not contributed to the improvement of social conditions in the territories where it is most representative and that contrary to expectations, it has increased the processes of inequality and has not had any effect on poverty.